The Effectiveness of the Labor Information System Website at the Cirebon Regency Labor Office - Delia Noviyanti; Yanto Heryanto (Al-Makki Publisher, 2026)
The Cirebon Regency Manpower Office issued a public service innovation in the form of an Employment Information System website which is an effort to support the implementation of e-government and improve the quality of employment services. However, in its implementation, there are still obstacles such as delays in updating information, limited human resources, and low utilization rates. This study aims to assess the extent of the effectiveness of the employment information system website and identify the inhibiting factors and efforts that occur in the implementation of the website. The method used was a qualitative descriptive approach with data collection techniques through observation, interviews and documentation. Using the analysis of the theory of the effectiveness of the Campbell J.P. program, namely the success of the program, the success of the targets, satisfaction with the program, the level of input and output, and the achievement of overall goals. The results of the research on the Employment Information System Website at the Manpower Office are quite effective in supporting public services, but there are those that are less effective in updating information, community utilization and human resources of website managers. Therefore, there is a need for a consistent improvement in information updates, strengthening website management, and developing interactive features so that the effectiveness of digital-based employment services can be continuously improved.